Something about the Weather. Using Digital Methods to Mine Geographical Conceptions of Europe in Twentieth-Century Dutch Newspapers - Van Eijnatten, Joris (BMGN - Low Countries Historical Review, 2019)
How was Europe portrayed as a geographical entity in the texts of weather reports published in Dutch newspapers between 1950 and 1990? To answer this ostensibly simple question, this article uses digital methods, including text mining and visualisation techniques. It shows that digital historical research offers a way of objectifying long-term, stable subjectivities. The Dutch perception of Europe that emerges from this qualitative analysis is remarkably slanted towards distinctions between a first, second and third-degree Europe, findings that may help explain the tenacious resistance to Europe as an inclusive political project. Hoe werd Europa als geografische entiteit afgebeeld in weerberichten in Nederlandse kranten in de periode tussen 1950 en 1990? Om deze schijnbaar eenvoudige vraag te beantwoorden worden in deze bijdrage gebruik gemaakt van digitale methoden, zoals text mining en visualisatietechnieken. Het artikel toont aan dat digitaal historisch onderzoek een manier biedt om het bestaan van langdurige, stabiele subjectiviteiten te objectiveren. De Nederlandse perceptie van Europa die uit deze kwalitatieve analyse naar voren komt is opvallend gekleurd, met een duidelijk onderscheid tussen een eerste-, tweede- en derdegraads Europa. De bevindingen kunnen helpen om de hardnekkige weerstand tegen Europa als een politiek project te verklaren. De paginering van de online versie van dit artikel wijkt af van de paginering van de gedrukte versie, dit omwille van de verschillende plaatsing van de illustraties. Due to the divergent position of the illustrations, the page numbers of the online version of this article differ from the page numbers of the printed version.